If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6x + -5) = -52 Reorder the terms: 2(-5 + 6x) = -52 (-5 * 2 + 6x * 2) = -52 (-10 + 12x) = -52 Solving -10 + 12x = -52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 12x = -52 + 10 Combine like terms: -10 + 10 = 0 0 + 12x = -52 + 10 12x = -52 + 10 Combine like terms: -52 + 10 = -42 12x = -42 Divide each side by '12'. x = -3.5 Simplifying x = -3.5
| (4x+5)(2x-4)= | | 6p-5=-2p+7 | | 3.2=15.75+3.2d | | Log(400-R)=5.9 | | Ln(400-R)=5.9 | | (x-6)*(x-5)*(x-7)=0 | | 10p-9=-2p+5 | | n^2+n+34=a^2 | | z^4=-1+sqrt(3)i | | 8p-5=-2p+7 | | 14+-5=9 | | 5x-2(x+2)=13-3x | | -7-4x=49 | | 7x-3y+9=p | | 3x+x-8=0 | | 3x-11=4x+6 | | (-4)/(q)=(?)/(6q) | | 4p=12z | | log(x+2)+log(x-1)=log(13-2x) | | 9(x-2)=61.2 | | 6(x-2)=61.2 | | x*x*x*x-x*x*x-9x*x-11x-4=0 | | 4x+x+(3+2x)=3x(x-2) | | 2p+wr=r-7g | | https://media.education2020.com/evresources/4072-03-02-06-00_files/i0300000.jpg | | 3s^2-7s-4=0 | | (3-2m)/3=(5-4m)/4 | | 3x+8=6x+28 | | y-3x+4=0 | | 2(y-7)-3y=-(y-3)-12 | | Tan(4*x)=0 | | 3x+(x+5)=70 |